Choice trajectories in the biographies of leaders of non-state confessional drug rehabilitation centers - Irina E. Petrova; Eugene I. Dulesin (Семиотические исследования)
The article is devoted to the identification of trajectories of choices in the biographies of heads of non-state confessional drug rehabilitation centers, whose life paths include periods of personal drug addiction, experiences of successful rehabilitation, and stages of ministry as assistants and heads of rehabilitation centers. The events in the personal biographies of the respondents are considered as a spectrum of points of social uncertainty, in which choices had to be made, influencing the determination of the further direction of their life paths. The use of the biographical approach, together with the sociology of the life course and the concept of agency, allows us to consider choice as an active position in the construction of one’s own life trajectory through the rejection of previous paths and the acceptance of new ones, as well as to study the process of formation of resources necessary for making decisions that influence the direction of the respondents’ life courses. Based on the analysis of a series of 20 in-depth interviews with the heads of non-state confessional drug rehabilitation centers, the key moments of making choices in the respondents’ biographies were identified, and the resource base – including the personal experience of drug addiction and successful rehabilitation – was determined. The formed agency is the basis for the choice of further ministry in the field of rehabilitation, agency.